CLINICAL STUDY OF CONTRACEPTIVE ACTIVITY OF TALISPATRA AND GAIRIKA - Kapila, Shete (Pimpale) (International Journal of Ayurveda and Pharma Research, 2016)
The world population is increasing much faster. Many socio-economic conditions of people have also been adversely affected. Various side effects have been observed with modern contraceptive methods. In Ayurveda many contraceptive drugs are explained, According to Yoga-Ratnakar Talispatra with Gairika is considered as a potent contraceptive, hence to assess its clinical efficacy, Ovulatory effects, side effects of the formulation and to provide cost effective, safe and effective method of contraception and contribute to national health programme like family planning this study was under taken.Clinical study was conducted on 30 women, 15 in each group. In group I mixture of Talispatra (Taxus baccate) & Gairika (Red oxide) (10gm) a single dose was administered on 4th day of menstrual cycle with cold water. In group II tab Mala - D daily one administered from 5th day of M. C for 21 days, follicular study was done on 11th day of M. C. in each patient observed for 3 cycles.In clinical study test drug in group I had shown In Ist, IInd, IIIrd month Dominant Follicle observed in one woman (6. 66%), eight women (53. 33%), twelve woman (80%) respectively and endometrial thickness observed less than 7mm in ten women (66. 6%), 4 women (26. 66%) 3 women (80%) respectively the study drug shown, significant contraceptive activity in I month than II, III month and group II. But side effects were noted only in group II.Mixture of Talispatra & Gairika had shown significant contraceptive activity. It is effective, safe, acceptable, less expensive enough to obviate frequent administration & without medical supervision.